Appetite‐Related Responses to Overfeeding and Longitudinal Weight Change in Obesity‐Prone and Obesity‐Resistant Adults. Issue 2 (23rd January 2020) - Halliday, Tanya M.; Rynders, Corey A.; Thomas, Elizabeth; Bergouignan, Audrey; Pan, Zhaoxing; Kealey, Elizabeth H.; Cornier, Marc‐Andre; Bessesen, Daniel H.
Abstract : Objective: Appetite responses to 3 days of overfeeding (OF) were examined as correlates of longitudinal weight change in adults classified as obesity prone (OP) or obesity resistant (OR). Methods: OP ( n = 22) and OR ( n = 30) adults consumed a controlled eucaloric and OF diet (140% of energy needs) for 3 days, followed by 3 days of ad libitum feeding. Hunger and satiety were evaluated by visual analog scales. Ghrelin and peptide YY (PYY) levels were measured during a 24‐hour inpatient visit on day 3. Body weight and composition were measured annually for 4.0 ± 1.3 years. Results: Dietary restraint and disinhibition were greater in OP than OR (mean difference: 3.5 ± 1.2 and 3.3 ± 0.9, respectively; P < 0.01) participants, and disinhibition was associated with longitudinal weight change ( n = 48; r = 0.35; P = 0.02). Compared with the eucaloric diet, energy intake fell significantly in OR participants following OF ( P = 0.03) but not in OP ( P = 0.33) participants. Twenty‐four‐hour PYY area under the curve values increased with OF in OR ( P = 0.02) but not in OP ( P = 0.17) participants. Furthermore, changes in PYY levels with OF correlated with measured energy intake ( r = −0.36; P = 0.01). Conclusions: Baseline disinhibition and PYY responses to OF differed between OP and OR adults. Dietary disinhibition was associated with 5‐year longitudinal weight gain. Differences in appetite regulation may underlie differences in propensity for weight gain.